Thalamic CGRP neurons define a spinothalamic pathway for affective pain - Sukjae J. Kang; Shijia Liu; Jong-Hyun Kim; Dong-Il Kim; Tae Gyu Oh; Jiahang Peng; Mao Ye; Kuo-Fen Lee; Ronald M. Evans; Martyn Goulding; Sung Han (Proceedings of the National Academy of Sciences, 2025)
Pain is both a sensory and emotional experience caused by various harmful stimuli. While numerous studies have explored peripheral and central pain mechanisms, the specific neural circuits linking the spinal cord to the brain remain poorly defined. In this study, we demonstrate the involvement of calcitonin gene-related peptide (CGRP)-positive neurons in the parvicellular part of the subparafascicular nucleus (SPFp) in pain. Tracing revealed that CGRP neurons in the SPFp (CGRP SPFp ) receive projections from the dorsal horn. Increased calcium activity was observed in CGRP SPFp neurons during mechanical, thermal, and inflammatory stimuli. Genetic silencing of these neurons resulted in reduced pain responses in animals. Furthermore, optogenetic activation of CGRP SPFp neurons induced aversive memory but did not alter mechanical or thermal pain thresholds. This study reveals a distinct neural circuit involving CGRP SPFp neurons that mediates pain, which differs from CGRP neurons in the parabrachial nucleus. Understanding these circuits could lead to better pain treatments with fewer side effects.